Prototype of cascade level and flow control system on steam drum based on IoT - Astrie Kusuma Dewi; Andhika Darussalam; Pujianto Pujianto; Chalidia Nurin Hamdani; Natasya Aisah Septiani (JURNAL INFOTEL, 2023)
In the industrial field, boiler functions to heat a fluid in the form of water, the boiler has a part which is a steam drum which has a function to produce steam for use for utility needs, and a steam turbine, in practice, the state of the water level must be maintained at the desired value or set. point so that carryover does not occur, and in overcoming these problems a control system is needed. This control works by comparing the value of the sensor and the set point, then gives an output signal to correct that to speed up the response, so it is necessary to use a cascade control configuration that adds an input flow control as a slave control. In this prototype, the cascade level control serves to control the level process. In addition, the human-machine interface has been designed to monitor processes in real-time. In addition, this prototype is equipped with an Internet of Things system that functions for the monitoring process as long as it is always connected to the internet. To run the control system, parameter control is needed, in this project the PID parameter setting uses the Ziegler-Nichols method with the parameter Kp level=20.25; Ki level = 1.51; Kp Flow = 5.14; Ki flow = 2.2.